The experience of college undergraduates : degrees of transformation - French, A. A. (Cranfield University, 1997)
Following discussions with staff (7), successive and progressive individual interviews were held throughout their course with a small group of undergraduates (8) taking a combined studies degree in a college of higher education. Data were not confined to the course but took a broad view, including their formal and informal lives and the interplay between them. What the informants faced and how they changed are all clearly illustrated. The students' experiences are described and analysed using a concept of transformation as achievement and process. This concept is compared with other theories of transformation in the educational literature. It is argued that the students faced three phases of exposure: social exposure, the need to be accepted in a new setting; academic exposure, having to take seriously the formal judgements of tutors and sustain the will to study; and the 'final' phase of personal exposure, self- awareness and letting go of dependence. Commitment, routine and support were central to success. Although the concept of education which informs it must reflect the values of the writer, the argument is firmly grounded in the data. To obtain an authentic portrayal, the critical incident technique was deployed in an extended way, through a form of questioning, which, it is suggested, could itself have a part to play in the tutorial role. The study contributes to a fuller understanding of students' college careers by offering an holistic perspective and filling a gap in higher education research. It was based on data from a few informants in a small distinctive college at a particular time, but its possible wider relevance for theory and practice are discussed.